Prevalence of Southern Leaf Blight of Maize in two major maize producing states of India - Vanlalhruaia; Mahapatra, Sunita; Chakraborty, Sunanda; Das, Srikanta (Journal of Cereal Research, 2022)
Southern corn leaf blight (SCLB) or Maydis leaf blight, caused by Bipolaris maydis, is an important disease of maize in the eastern and north-eastern part of India. Hence, to assess the severity and distribution of the disease in two distinct and major maize growing states i.e. Mizoram and West Bengal were selected. A roving survey was conducted under different agro-climatic conditions during the kharif season of 2019 and 2020 in three districts of West Bengal and as well as in Mizoram. The survey results revealed that SCLB was more prevalent in the plains of West Bengal in comparison to hilly areas of Mizoram. The mean SCLB incidence varied from 18.87% in Zemabawk, Mizoram to 63.22% in institutional farm, C-block, of BCKV, West Bengal. The mean disease severity ranged from 10.06 % in Muthi, Mizoram to 22.09% in Instructional Farm, Jaguli, BCKV, West Bengal. Both disease incidence and severity were highest at 99 DAS in all the locations surveyed. Successive surveys of SCLB in the maize growing belts across the country need to be conducted to develop a better understanding about the disease prevalence, intensity and severity under different agro-ecological conditions.